Relationship of relative poverty and social relationship on mortality around retirement: a 10-year follow-up of the Komo-Ise cohort - Hirokazu Tanaka; Atsushi Miyawaki; Satoshi Toyokawa; Yasuki Kobayashi (Komiyama Printing Co. Ltd, 2018)
Abstract Background As society is aging, retirement takes on increasing importance for individuals in the later life. This study aimed to describe mortality before and after retirement in the Japanese middle-aged/elderly with special attention to socioeconomic position and social relationships. Methods We conducted a 10-year follow-up study (the Komo-Ise cohort study) and assessed mortality according to socioeconomic positions (relative poverty and occupation) and social relationships (e.g., marital status, living alone, and social support) in workers and the retired. Relative poverty was defined as a household equivalent income of 12,700 US dollars (1.37 million Japanese Yen) or less in 2000. Stratified analyses were conducted according to sex in two groups of employment status: the workers and the retired. Adjusted hazard ratios (HRs) were calculated using the Cox proportional hazard model. Results We included 5534 individuals. Of these, 3360 were men (working, 2499; retired, 861) and 2174 were women (working, 1306; retired, 868). We observed 610 deaths (475 in men and 135 in women) during the study period. Relative poverty was a significant risk factor for death (HR 1.52, 95% confidence interval [CI] 1.07-2.14) among retired men but not among working men (HR 1.20, 95% CI 0.79-1.83). Among workers, self-employed men showed a significantly higher hazard of death (HR 1.57, 95% CI 1.09-2.25) than white-collar employees. Retired men who lacked participation in social activities were more likely to die than those who did not (HR 1.44, 95% CI 1.06-1.94). All results, except marital status, indicated non-significant associations in women. Conclusions Relative poverty and lack of social engagement may be related to high mortality risk in retired men. Further studies are needed to assess the health status among the middle-aged/elderly population around retirement.